Pediatric Hospital Medicine Elective - Jennifer Walthall; Michele Saysana; Jeffrey Sperring (Association of American Medical Colleges, 2009)
Abstract Pediatric hospital medicine is a relatively new field in pediatrics and has seen rapid expansion in community and academic hospitals. Residents in training are often exposed only to modeling of clinical aspects of hospital medicine and are also time limited in the ability to experience the administrative components, quality improvement, transitioning of care, and opportunity for procedures in which practicing hospitalists must have competency for daily practice. Thus, we created this pediatric hospital medicine elective to provide upper-level residents with exposure to the various roles of pediatric hospitalists. This pediatric hospital medicine elective curriculum includes goals and objectives for the rotation; a novel elective menu that allows for individualized learning; a calendar of events for residents that includes administrative meetings, preparation time for team didactics, and protected time for clinical pathway development; coding and billing pre- and posttests; a billing and coding lecture series; a procedural sedation introductory lecture; reading materials; an advocacy project for the ward; and mentoring session worksheets. During the first 6 years of our pediatric hospital medicine service, there was minimal resident exposure to the paradigm and no formal training venue for those interested in pursuing this career. We did a needs assessment survey in our residency to determine if residents wanted more exposure to what pediatric hospitalists do. Our residents responded that they were interested in pediatric hospital medicine as a specialty, would participate in a hospital medicine elective, and thought that hospital medicine was important to patient care. Thus, we developed this resource. On the basis of learner feedback from focus groups, which had 100% participation, we have modified this curriculum to incorporate detailed description of the menu options, as well as expanded the procedural sedation component.